Incidence of Cardiotoxicity Associated with The Use of Pegylated Liposomal Doxorubicin in Gynecologic Malignancies - Phansenee, Supreechaya; Angkatavanich, Teerit; Rittiluechai, Kristsanamon; Intharaburan, Suttida (Biomedical Sciences and Clinical Medicine, 2024)
Objective This study aims to evaluate the incidence of cardiotoxicity in patients with gynecologic cancer undergoing pegylated liposomal doxorubicin (PLD) treatment and to identify risk factors for developing changes in the left ventricular ejection fraction (LVEF). Methods A retrospective analysis was conducted on patients with gynecologic malignancies who had received PLD treatment at Phramongkutklao Hospital from January 2013 through December 2022. Cardiotoxicity was defined as a confirmed diagnosis of congestive heart failure or a decline in LVEF of 10% or more. Spearman’s correlation and mixed modeling were used to analyze the relationship between patient factors and MUGA variations. Results A total of 34 patients were included in the study. The median number of PLD cycles was six, with a median cumulative dose of 240 mg. No patient experienced doxorubicin-induced cardiotoxicity. Among the 19 patients with available pre- and post-treatment LVEF measurements, no significant decline in LVEF was observed following PLD (MD 6.6%, p = 0.124). However, Spearman’s correlation analysis revealed a negative correlation between high cumulative PLD doses (exceeding 1,500 mg) and LVEF change (coefficient = -0.53, p < 0.001). Mixed model analysis suggested a potential association between higher body mass index (BMI) and decreased LVEF post-treatment (β = -1.21, p = 0.036), while diabetes may be associated with improved LVEF outcomes (β = 12.18, p = 0.033). Conclusions There were no cases of cardiotoxicity after PLD treatment. A potential association between higher BMI and decreased LVEF was found. A high cumulative PLD dose is correlated negatively with LVEF change. Cardiac monitoring is recommended for selected patients, particularly those who are obese or have received cumulative PLD doses exceeding 1,500 mg.